Anti-Vibrio from Ethyl Acetate Extract of Sponge- Associated Fungus Trichoderma longibrachiatum - Sedjati, Sri; Ambariyanto, Ambariyanto; Trianto, Agus; Ridlo, Ali; Supriyantini, Endang; Yudiati, Ervia; Firmansyah, Teguh (Jordan Journal of Pharmaceutical Sciences, 2021)
Some of Vibrio spp. bacteria are pathogenic to humans and other organisms, including cultured fish or shrimp. This study aimed to determine the activity of ethyl acetate extract of Trichoderma longibrachiatum as an anti-vibrio fungus. The test bacteria used were: Vibrio harveyi, Vibrio anguillarum, Vibrio vulvinificus, and Vibrio parahaemolyticus. The fungus was cultured using Malt Extract Agar (MEA) medium for 9 days at 27oC (static conditions, 24 hours dark, pH 5.6, and salinity 60 ppt). Extracts obtained by maceration using ethyl acetate, then the extract is partitioned using water-methanol 70:30 and ethyl acetate. Each fraction was concentrated to obtain polar-ethyl acetate (PE) and semipolar-ethyl acetate (SPE) extracts. The components of the constituent extract were traced with a Thin Layer Chromatography (TLC) and followed by ultraviolet spectrophotometry. The anti-vibrio activity was determined based on the value of Minimum Inhibitory Concentration (MIC). The results of the study showed that SPE was more potential to be used as anti-vibrio. The strongest activity was able to inhibit the growth of Vibrio vulvinificus with 256 μg mL-1 MIC value, while the weakest was against Vibrio parahaemolyticus with 1.024 μg mL-1 MIC value. In conclusion, SPE has the potential to be developed as an anti-vibrio compound, particularly against Vibrio vulvinificus.